Assessment of Agrocenosis Adaptability of Winter Wheat in the Conditions of the Foothill Zone of the Central Caucasus - Manukyan, Irina; Miroshnikova , Elena; Basieva, Madina; Doguzova, Nino (KnE Life Sciences, 2021)
This paper presents the results of multi-year research on the adaptability of winter wheat varieties to the conditions of the foothill zone of the Central Caucasus. Characteristics such as ductility and stability were used to assess varieties for conformity to the cultivation conditions. Plant homeostaticity served as the indicator of ontogenetic adaptability. Phenological observations and reports were carried out according to the state variety testing methodology. The species composition of weed vegetation was established using the Agroecological Atlas of Russia. Conventional insect accounting methods were used to consider phytophages and plants damaged by them. It was established that the dominant pests of winter grains in the early periods of vegetation include phytophage bugs and cereal leaf beetle Oulema melanopus L. The maximum number of phytophage bugs was noted during the earing-flowering period. The proportion of pathogens of spike Fusarium head blight, tan spot and Septoria spot prevailed in the pathogenic complex. In total, 36.7% of varieties, including Kuma, Deya, Esaul, Starshina, Delta, Nota and Antonina, were medium-resistant to Fusarium head blight damage. According to the results of a comprehensive assessment of winter wheat selection by the parameters of adaptability, productivity and resistance to diseases, highly plastic genotypes responsive to environmental factors were distinguished: Kuma, Deya, Veda, Tanya, and List 25 (bi = 2.2; 2,3; 2,1). The selection of varieties was based on the adaptive properties of winter wheat. Fusarium head blight decreased by 20.8% in the mixed variety Batko+Deya, and the yield of mixed variety crops increased by 9%. Methods for compiling mixed varieties and designing the mosaics of varieties in the area of grain agrocenosis are recommended. Keywords: winter wheat, sustainability of agrocenosis, productivity, ecological plasticity, mixed varieties